HUBUNGAN HUBUNGAN AKTIVITAS FISIK DENGAN KEJADIAN DIABETES MELITUS TIPE 2 DI PUSKESMAS BANJAREJO - Lutfiah, Nabilla Fitriq Lailattul; Ratnawati, Riska; Wibowo, Pipid Ari (Jurnal Kesehatan, 2025)
Diabetes mellitus was a chronic disease that lead to metabolic disturbances, which characterized by an increase in blood glucose levels above normal. The incidence of type 2 diabetes mellitus is among the top 10 disease trends in the city of Madiun. Based on data from the Banjarejo Health Center, the number of type 2 diabetes mellitus patients in the elderly aged 60-74 years in 2022 was 58 cases. The objective to analyze the relationship between physical activity and the incidence of type 2 diabetes mellitus of Banjarejo Health Center. The research method with a case-control study design. The population includes all patients with type 2 diabetes mellitus in the working area of Banjarejo Health Center. The sample consist 78 respondents. The sampling technique used simple random sampling. The data this study obtained through questionnaires and interviews. The data analysis includes univariate analysis and bivariate analysis using the Chi-Square test. The research results revealed a relationship between physical activity and the occurrence of type 2 diabetes mellitus (P value = 0.000; OR = 14.481; 95% CI = 3.823-54.858).